Obtención y aplicación del extracto de aloe vera en la etapa de multiplicación in vitro de tres variedades comerciales de musa - Arias Pineda, Danny Leander (2010)
In the laboratory of vegetable Biotechnology of the Ability of Agricultural Sciences he/she was carried out the present rehearsal with the following objectives: To determine the stimulating effects of the Aloe vera in the multiplication stage; to evaluate which responds to the different dosages of Aloe vera of the three muse varieties; to compare costs of the means of multiplication Murashige Skoog more an organic component. It was used apexes of young hijuelos of 1 m of height. you diseccionaron the cormos until a height of 10 cm and 4 cm of wide, left them to him with commercial chlorine during 20 min. he/she is carried out them a triple laundry with distilled water sterilized during 5 min each laundry and lastly he/she ends of diseccionar the material until leaving it 0,5 cm of point of growth and 0,5 cormo cm and you the siembra in a half initiation. The means that Murashige Skoog was used (MS) suplementando with macroelementos, microelementos, sulfate of magnesium, iron solution, vitamins, myo-inositol, hormones (BAP), sugar and agar, but the extract of Aloe vera; the pH should be adjusted at 5,8. A factorial arrangement AxB was used, in a design completely randomizado, where TO = three varieties, B = four means, and five repiticiones giving a total of 60 experimental units. There was not significancia between the means and varieties being the means of MS 100% and MS 80% + sábila 20% the best behaviors. For that that if it diminishes the means of cultivation the sábila it can maintain the levels of necessary substances for the development of the plántulas. The varieties Cavendish G and Willians responded to the dosages. The production costs for the means MS 100% is of $11,25, for MS 80% + sábila 20% is of $10,65 and the means MS 60% + sábila 40%, MS 40% + sábila 60% is of $ 9,15 dollars.